Development and evaluation of rabies health education module (RAHEM) to improve knowledge and attitude among dog owners in Kelantan - Basir, Mohammad Fazrul Mohammad (2025)
Background: Rabies remains a global public health concern, particularly among dog owners, due to persistent gaps in knowledge, attitudes, and practices (KAP) related to its prevention. Existing health education initiatives often lack depth and long-term sustainability. This highlights the need for a structured and evidence-based module to enhance rabies-related awareness and promote positive attitudes among dog owners. Integrating the One Health approach ensures that rabies prevention efforts address not only human health but also the role of animals and the environment. Objectives: To determine the levels and associated factors of rabies-related KAP, as well as to develop, validate and evaluate the RaHEM in improving these outcomes among dog owners in Kelantan, Malaysia. Methodology: This study was conducted in three phases. Phase one employed a cross-sectional design with 232 adult dog owners completing the validated questionnaire, and logistic regression identified factors associated with KAP. Then, the RaHEM was developed using the Analysis, Design, Develop, Implementation and Evaluation (ADDIE) framework including the validation process through content and face validation during the second phase. Phase three followed by involving a randomized controlled trial with 80 participants to evaluate knowledge and attitude at one-month post-intervention. MANOVA was used to analyse score changes between the intervention and control groups. Result: The cross-sectional study revealed that 53.0% of participants had good knowledge, 26.7% exhibited positive attitudes, and 40.0% demonstrated good practices toward rabies prevention. Key factors associated with these outcomes included education status, prior attendance at rabies awareness programs, number of pet dogs, duration of dog ownership, household size, knowledge scores, age groups, and dog acquisition methods. The final module includes 5 main topics, 11 units, and 32 learning objectives. All the Content Validation Index (CVI) and Face Validation Index (FVI) scores exceeded the acceptable threshold of 0.83 across all unit, topic, and overall module. The randomized controlled trial demonstrated a significant difference between the intervention and control groups (Wilks' λ=0.627; F(2,77)=22.921; p-value<0.001; partial η²=0.408). Post hoc Bonferroni-adjusted pairwise comparisons revealed that the intervention group showed significantly greater improvements observed in the intervention group for both knowledge and attitude score. Conclusion: The study reveals the low levels of rabies-related KAP among Kelantanese dog owners that emphasize the need for a structured educational module while identifying key associated factors through the lens of One Health. The successful development, validation, and proven effectiveness of RaHEM underscore its potential as an impactful health education tool, particularly in enhancing knowledge and attitudes synergistically. This module reinforces its role in strengthening rabies prevention efforts, aligning with global and national goals to eliminate dog-mediated human rabies deaths by 2030.